Inhibition of Corrosion: Mechanisms and Classifications in Overview - Mohammed H. Al-mashhadani; Ahmed A. Ahmed; Zainab Hussain; Salam A. Mohammed; Rahimi M. Yusop; Emad Yousif (Al-Qadisiyah Journal of Pure Science, 2020)
Corrosion inhibitors are substances, which added to the metallic materials to keep them from the destructive surroundings. Presently, inhibitors have been used in many industrial regions such as chemical and oil production because they are easy to modify their chemical structure according to their needs. In this review, the inhibitors are classified according to the mechanism of inhibition. It also shows the type of corrosion inhibitors that take from a natural source and some examples about this type and its work mechanism